Research on Regional Financial Development and Local Economic Transformation and Upgrading - Wang, Ruixue (Economics & Management Review, 2020)
Based on the research at home and abroad, this paper systematically sorts out the impact mechanism of financial development and local industrial transformation and upgrading, analyzes the internal relationship between financial development and local industrial structure upgrading, and makes an empirical study on this major problem by using the data of Shandong Province from 2003 to 2019. It is found that there is a long-term equilibrium relationship between financial development indicators and industrial transformation and upgrading indicators in Shandong Province. The contribution of local financial development to the tertiary industry is the largest, while the contribution to the primary industry is relatively small. Therefore, in order to further promote the transformation and upgrading of local economy in Shandong Province, we should optimize the financial structure, improve the quality of financial products and services, and improve the financial system.